2009
DOI: 10.1371/journal.pone.0007409
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to Care: Duration of Untreated Psychosis from Karachi, Pakistan

Abstract: BackgroundSubstantial amount of time is lost before initiation of treatment in Schizophrenia. The delay in treatment is labelled as Duration of Untreated Psychosis (DUP). Most of these estimates come from western countries, where health systems are relatively better developed. There is dearth of information on pathway to care from developing countries.Methods and ResultsPatients with ICD-10 based diagnosis of Schizophrenia were enrolled by convenient method of sampling. The pathway to care was explored through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 23 publications
0
38
3
1
Order By: Relevance
“…36 However, other studies did not show any association between marital status and DUP. 10,16 Our result might be understood by considering the impact of culture on decision making to seek treatment. This might be influenced by lack of awareness of mental illness and stigma.…”
Section: Marital Statusmentioning
confidence: 92%
See 1 more Smart Citation
“…36 However, other studies did not show any association between marital status and DUP. 10,16 Our result might be understood by considering the impact of culture on decision making to seek treatment. This might be influenced by lack of awareness of mental illness and stigma.…”
Section: Marital Statusmentioning
confidence: 92%
“…9 Another study was conducted in Karachi, Pakistan, and showed that because of the lack of a primary care system, most of the psychotic patients contacted psychiatrists directly. 10 Understanding the importance of early diagnosis and treatment is an important step to eliminate this delay and mitigate its impact on the prognosis of the disease. The first stage of help seeking is the decision to seek help and this is what seems to be prone to most delay.…”
Section: Introductionmentioning
confidence: 99%
“…Second, economic factors may impair access to mental health services. For a low-income population, it may simply be too expensive to afford psychiatric treatment [ 9 10 , 12 13 ]. Third, the fear of stigmatization and discrimination associated with psychosis can prevent patients, or their family members, from acknowledging the presence of mental disorder and therefore seeking help [ 8 – 10 , 14 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, much of the research concerning DUP has focused on one site only [ 2 , 12 , 16 ], without direct comparison in different cultures and religions. In addition, previous studies focused on patients’ [ 8 – 9 , 11 , 14 , 17 20 ] or caretakers’ perspectives [ 21 22 ], but research on DUP with diverse population or perspectives from both patients and their family members are especially scarce. In this research, both respects were taken into consideration, and the above barriers were assessed in Changsha, China and Mauritius, which are geographically, socially and culturally different.…”
Section: Introductionmentioning
confidence: 99%
“…[51][52][53] Given the enormous risks associated with relapse and the absence of reliable relapse predictors, longer periods of treatment are increasingly advocated. 5 Clinicians may however sometimes decide to discontinue antipsychotic treatment in a particular patient, for example, due to uncertain or changed diagnosis. In such a situation, as with oral antipsychotics, depot antipsychotics may be discontinued at any stage of treatment.…”
Section: Considerations When Using Depot Antipsychotics In Early Illnessmentioning
confidence: 99%